STUDY DESIGN BEGINNING TO AHCII DTMF DECODER MICROCONTROLLER AT89C2051 ( CASE STUDY TOOLS PHONE NUMBER ON LCD VIEWER, THE SED 1200 ) - Dwi Estuning Impiyanti; Drs. Linga Hermanto, MMSI Drs. Linga Hermanto, MMSI (Jurnal Sistem Komputer, 2002)
Viewer numbers are very commonly used in telephone on-telephone kiosks. To theauthors tried to make the tool viewer phone numbers that can be used at home, in theoffice and anywhere.Outstanding aircraft now mostly use the digital receiver. Digital telephone usingDTMF tones to identify the phone number buttons are pressed. To read the DTMFtones required special components that can detect these tones and translate them intobinary code. Binary code is then converted into ASCII coded signal by themicrocontroller to display on the LCD. LCDs are used here is a cheap LCD dotmatrix LCD is SED1200. Compared with other LCD LCD is relatively cheaper.